Being Eager to Prove Oneself: U-Shaped Relationship between Competence Frustration and Intrinsic Motivation in Another Activity - Fang, Hui; He, Bin; Fu, Huijian; Meng, Liang (Frontiers in Psychology, 2017)
Competence frustration has been consistently found to undermine intrinsic motivation in the same activity. However, the relationship between competence frustration in a preceding activity and intrinsic motivation in a subsequent one remains unclear. In order to explore this relationship, self-reported data were collected from 617 undergraduate students of a large comprehensive university in south China, who took various courses immediately before taking a less-demanding one. Results suggested a U-shaped relationship between students’ competence frustration in a preceding course and intrinsic motivation in a subsequent one. To be specific, for students whose competence frustration reached the inflection point, a restoration process would be activated if the current course would help restore their competence. Importantly, competence frustration in a preceding course was found to positively predict the intrinsic motivation level in a subsequent course. As far as we know, this is the first study to reveal the potential effect of need frustration outside of the primary thwarting context, which complemented and extended existing literatures on intrinsic motivation.